Evaluation of the effectiveness of local electrical stimulation with axial load in the correction of combined flat feet and postural asymmetry by electrical stimulation - V. V. Karmazin; A. V. Slivin; S. A. Parastaev (Лечащий Врач, 2023)
The article presents the results of applying the method of corrective action in case of combined (longitudinal-transverse flat feet and postural asymmetry by electrical stimulation using various pulsed currents to change the functional state of muscles and nerves for therapeutic purposes in combination with a foot massager of the thermotherapeutic personal myostimulating apparatus. The scientific study was organized by the All-Russian public organization "Russian Association for Sports Medicine and Rehabilitation of Patients and Disabled People" on the basis of the Federal State Budgetary Institution Federal Scientific and Clinical Center for Sports Medicine of the Federal Medical and Biological Agency of Russia by a doctor in physical therapy, candidate of medical sciences Karmazin V. V. The purpose of this study was to evaluate the effect of the myostimulating function of the device on the postural stereotype of patients with combined flat feet and revealed, according to baropodometry, asymmetry in the distribution of axial load under the feet.The study involved 10 patients with diagnosed flat feet of varying severity and identified support asymmetry of more than 5% displacement to the right or left. All patients included in the group of subjects underwent procedures on the apparatus. Evaluation of the effectiveness of the electrostimulating effect was made on the basis of the subjects undergoing a course of correction with the electromyostimulation apparatus in the amount of 7-8 procedures with the passage of baropodometry after each procedure. According to the results of the procedures, 70% of the subjects, according to baropodometry, revealed a decrease in pressure in the area of the longitudinal arch of the foot, towards which the initial shift of the general center of pressure under the feet was observed. It was also found that the device really has an effective electromyostimulating effect on the muscles of the foot. The need for further scientific study on the impact of the device (electromyostimulation in combination with hyperthermia) and the creation of scientifically based programs for methods of correcting not only flat feet, but various foot pathologies, including those accompanied by pain syndrome of varying severity (plantar fasciitis, stress fractures of bones) metatarsus, tendonitis, ligamentitis, etc.).